L’image du père et du jardin : Jane Eyre de Charlotte Brontë et WideSargasso Sea de Jean Rhys - Anne-Marie Baranowski (Revue LISA)
Though no father actually appears as a character either in Jane Eyre or in Wide Sargasso Sea, the father figure looms large in both novels, as a complex, protean and paradoxical entity, playing a crucial part in the fate of the protagonists. Jane Eyre and Antoinette Cosway are orphaned at an early age, Rochester’s father is depicted as remote and insensitive; the surrogate fathers —Antoinette’s stepfather, Jane’s uncles— mostly fail when they try to replace the missing one. Rochester himself is an ambiguous character who appears in both novels as a son, lover and husband on the one side, as a father figure on the other. In Wide Sargasso Sea he acquires through his marriage to the heiress Antoinette Cosway a legal authority which he eventually uses to destroy his wife; in Jane Eyre he first appears as the wealthier, more knowledgeable, stronger character before he discovers a female counterpart who does more than merely hold her ground.These different aspects of the father figure are closely linked to the motif of the garden which mirrors the inner development of the —mostly— female characters. It is not entirely similar to nature itself, though it is part of it; the latter means in both novels lethal dangers and elemental violence, whereas the garden is a sheltered place. In Wide Sargasso Sea, the debased garden of Coulibri simultaneously conveys a distorted, though by no means untrue reflection of the father figure and a sanctuary from the harshness of the outside world. It also means a place of peace and of simple joys for Jane Eyre, making up for the deprived life at the Lowood boarding school; but contrasting with Coulibri it does not preclude the contact with the outside world which she actually longs for. Hence the garden mirrors the crucial moments and experiences in the lives of both heroines, including love, married life and loss.